Giustina Renier Michiel traduttrice di Shakespeare: il caso dell’«Ottello o sia il Moro di Venezia» (ACME, 2020)
This contribution aims to analyse a small piece of Shakespeare’s reception in Italy in the late eighteenth century. It examines the Ottello translated by Giustina Renier Michiel, the first full Italian translation of the famous Shakespearean tragedy. After a quick reference to the context in which this initiative of translation was born and to the fields of investigation still open, this study focuses on the first edition of 1797 and examines, with a philological and bibliological look, the subsequent new editions and the rich paratext of the editio princeps, trying to circumscribe the dossier génétique (editions in original language and also French translations) of the Venetian translator. The contribution contains also the analysis of a specific case-study, the last scene of the shakespearian tragedy (Act v, Scene ii): it gives us the opportunity to better understand the cultural operation started by the «dama veneta», its aims, its target audience and the stylistic, lexical and syntactical choices made by her, in a translated text that interweawes passages borrowed from Pierre Le Tourneur’s French version and more original solutions.